Pancreatobiliary type IPMN ; A Clinicopathological Analysis of 7 Patients - Matsuyama, Masahiro; Imaizumi, Toshihide; Hirabayashi, Kenichi; Okada, Ken-ichi; Tobita, Kosuke; Dowaki, Shoichi; Makuuchi, Hiroyasu (Nippon Shokaki Geka Gakkai zasshi, 2011)
We analyzed the clinicopathological features and treatment outcome of 7 subjects aged 64-79 years (male/female ratio: 5 : 2, mean age: 72 years) with pancreatobiliary (PB) intraductal papillary-mucinous neoplasm of the pancreas (PB IPMN) seen from 1991 to 2009. Of these, three were symptomatic, macroscopic IPMN determined in clinical imaging were 3 main duct and 4 branch duct. Histologically, one involved adenoma and six IPMN-derived invasive carcinoma. All underwent surgery, and three with severe stromal invasion postoperative chemotherapy. The three with distant metastases survived a mean 26.4 months, with two developing liver metastasis and one metastasis to the lungs and bones. The four surviving have remained disease-free a mean 30.7 months. The invasive cancer rate was high at resection. Histopathologically, the three recurrent cases showed severe lymphatic, venous, or perineural invasion or invasion to retropancreatic tissue. Recent pancreatic juice cytology in IPMN comfirmed its subclassifiability, histomorphologically, cytologically, and immunocytochemistrically, but treatment decisions require sufficient knowledge of PB IPMN clinicopathological behavior.